THE INFLUENCE OF MANAGEMENT INFORMATION SYSTEMS ON HR IN AN ORGANIZATION - Lubis, Windy Frestia; Nasution, Muhammad Irwan Padli; Sundari, Sri Suci Ayu (Bina Bangsa International Journal of Business and Management, 2024)
This research was written with the aim of seeing how important the influence of management information systems on HR in an organization is on decisions. Management’s ability to utilize information as a form of major influence in carrying out managerial functions will also determine the success or failure of the management concerned with achieving success in managing or managing the organization it leads. This study aims to determine how much influence management information systems have on human resources in a company or organization. This research is associative. Data collection techniques were obtained from the internet. In this day and age, current technological sophistication is needed by an organization. Some of these influences are influenced by needs within an organization to increase effectiveness and efficiency in data processing and can even minimize costs and increase the productivity of a company or organization. However, something that has a high positive impact does not cover the possibility of having a high negative impact as well.